Analysis of the Incidence of Pulmonary Tuberculosis in the Working Area of ​​the Independent Health Center, Palembang City in 2024 (HEALTH CARE: JURNAL KESEHATAN, 2024)
Pulmonary tuberculosis (TB) is an infectious disease that is still a major health problem in Indonesia. The increase in the incidence of pulmonary TB mainly occurs in individuals with abnormal nutritional status, smoking habits, and lack of preventive measures. This study aims to analyze factors related to the incidence of pulmonary TB in the working area of ​​the Merdeka Community Health Center, Palembang City, in 2024.This study used a case-control design and was conducted in June-July 2024. The study population was all pulmonary TB sufferers who were still undergoing treatment at the Merdeka Community Health Center, with a sample of 76 respondents consisting of 38 cases and 38 controls. Data was collected through questionnaires and observations, and analyzed using multiple logistic regression tests.The results showed that nutritional status, smoking habits, and preventive measures were significantly related to the incidence of pulmonary TB. Abnormal nutritional status, active smoking, and lack of preventive measures increase the risk of pulmonary TB. The logistic regression model shows that these three factors contribute significantly to an increased risk of pulmonary TB.The conclusion of this research is that improving nutritional status, reducing smoking habits, and increasing preventive measures are very important to reduce the risk of pulmonary TB incidents in the Merdeka Community Health Center working area.